Health Risk Assessment and Levels of Heavy Metals in Farmed Nile Tilapia (Oreochromis niloticus) from the Volta Basin of Ghana. (31st December 2021) - Magna, Emmanuel Kaboja; Koranteng, Samuel Senyo; Donkor, Augustine; Gordon, Christopher
Abstract : Heavy metals (Pb, Cd, As, Mn, Fe, Zn, Cu, Ni, and Cr) are some of the most toxic elements that can bioaccumulate from sources linked to human activities, such as industry and agriculture. This study quantifies the concentrations of several heavy metals in caged tilapia found in Ghana's Volta Basin and assesses the associated health risks. The levels of heavy metals in the tissues of Oreochromis niloticus from three cage farms ( N = 52) were determined using Atomic Absorption Spectrometry (AAS). The implication for human health was assessed using several risk assessment techniques. Fe (50.11 ± 10.22 mg/kg) and Cr (0.31 ± 0.07 mg/kg) had the highest and lowest accumulated metal concentrations, respectively. Heavy metal concentrations in tilapia tissue from fish farms were ordered as follows: Fe > Mn > Zn > Ni > Cr (farm A), Fe > Zn > Ni > Mn (farm B), and Fe > Mn > Zn > Ni > Cr (farm C). All metals had an estimated daily intake (EDI) below the threshold, and mean differences between sample farms were not statistically significant. Similarly, the values of target hazard quotients (HQs) and hazard indices (HIs) were less than one. According to the risk assessment results, eating tilapia from farms posed no risk to human health. The presence of Mn, Fe, and Ni concentrations above the maximum level in the fish, on the other hand, suggests that they may affect fish health.